A copper-tungsten contact material, a contact and a method of manufacture

CN122898780APending Publication Date: 2026-10-13CHINA ELECTRIC POWER RESEARCH INSTITUTE CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610748733.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-28
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0006]本发明的目的是解决现有技术铜钨触头耐电弧烧蚀性不足以及与导电杆连接可靠性差的问题

Benefits of technology

本发明通过成分优化、结构设计与工艺改进的协同创新,实现了800kV 80kA极端工况下铜钨触头材料综合性能的突破性提升。首先,在触头本体中引入了由钴、镍和氧化镧按特定比例组成的多元复合添加剂,其原理在于:钴和镍在高温烧结过程中能与钨和铜发生微合金化,显著改善钨与铜之间的润湿性,促使铜液更充分地填充钨骨架间隙,从而大幅提高钨铜界面结合强度;同时,氧化镧作为弥散强化相,能够有效钉扎钨晶界,抑制高温下钨晶粒的异常长大和高温蠕变。基于此原理,该成分设计使得材料致密度提升至99.2%以上,消除了内部微观孔隙,有效避免了电弧作用下的局部优先击穿,更细化了晶粒,使材料在80kA高能量电弧冲击下的抗熔化、抗喷溅能力显著增强,烧蚀深度大幅降低,有效避免了触头轮廓变形和电场畸变。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a copper-tungsten contact material, a contact and a preparation method. The contact comprises a contact body and a conductive rod; the contact body is a copper-tungsten alloy composite material, and the composition comprises 75-85% of W, 15-25% of Cu and 0.3-0.8% of a multi-component additive in terms of mass percentage; the additive is composed of Co, Ni and La2O3 in a mass ratio of 1-2:0.5-1:1; the conductive rod is a copper-chromium-zirconium alloy; and the contact body and the conductive rod form a metallurgical bonding interface through high-temperature diffusion welding. The preparation method comprises the following steps: raw material high-energy ball milling, pressing forming, high-temperature pre-burning, pressure infiltration, vacuum diffusion welding and solid solution aging heat treatment. Through composition optimization and process coordination, the application refines the grain and significantly improves the material density and the interface bonding strength, solves the problems of poor ablation resistance of the traditional contact and easy cracking of the welding interface, and meets the extreme working condition requirements of the 800kV 80kA extra-high voltage circuit breaker.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrical materials technology, specifically relating to a copper-tungsten contact material, a contact, and a preparation method thereof. Background Technology

[0002] In recent years, with the rapid development and large-scale interconnection of power systems, the coverage and transmission capacity of ultra-high voltage (UHV) AC and DC transmission lines have been continuously improved. While the large-scale interconnection of power grids has enhanced the system's mutual power supply, power transfer capabilities, and operational reliability, it has also brought a severe technical challenge: a significant increase in the system's short-circuit current level. Currently, in some load-dense areas and areas with concentrated power supply access, the short-circuit current of 500kV and 750kV power grids has generally exceeded the standard. It is expected that in the future, the short-circuit current of UHV power grids will also exceed the current maximum breaking current limit of 63kA for circuit breakers. Once the short-circuit current exceeds the breaking capacity of the circuit breaker, it will directly affect the timely clearing of faults and the stable operation of the power grid. Existing measures to address excessive short-circuit current often come at the cost of weakening the system's operational flexibility, reliability, and economy, and are unable to fundamentally resolve the prominent contradiction between further power grid development and limiting short-circuit current.

[0003] As a critical device for fault isolation in power systems, circuit breakers require their core component, the arc contact material, to withstand extremely high arc erosion and intense mechanical impact during the breaking process. Currently, conventional 550kV and 800kV circuit breakers commonly use copper-tungsten alloy as the arc contact material. However, the short-circuit breaking capacity of existing copper-tungsten contact materials is typically limited to around 63kA. When faced with extreme operating conditions requiring a short-circuit breaking current of 80kA, existing materials exhibit significant performance bottlenecks, making it difficult to meet the stringent requirements of higher voltage levels and larger short-circuit currents.

[0004] Specifically, existing copper-tungsten contact materials suffer from the following main defects under extreme 80kA conditions: First, insufficient resistance to arc erosion. The 80kA level of arc energy is extremely high, and traditional homogeneous copper-tungsten contacts are prone to severe melting and spattering at the arc root, leading to rapid deformation of the contact profile and subsequent electric field distortion, severely affecting breaking performance. Second, difficulty in matching comprehensive mechanical properties. To meet ablation resistance requirements, the arc-initiating end of the contact usually needs a high tungsten content, but a high tungsten content significantly increases the overall brittleness of the material, making it prone to fracture under stress and when connected to the conductive rod. Currently, the industry mostly uses brazing to connect the copper-tungsten head to the chromium-zirconium copper tail, but this traditional welding method has inherent problems such as high weld interface resistance and easy softening of the weld heat-affected zone. Finally, abrupt changes in interface composition lead to severe thermal stress. In traditional layered contact structures, the composition of the copper-tungsten layer and the chromium-zirconium-copper layer differs greatly, and their coefficients of thermal expansion are extremely mismatched. Under the repeated impact of high-temperature electric arcs, fatigue cracks are easily generated at the interface and propagate rapidly, seriously threatening the operational safety and service life of the circuit breaker.

[0005] In summary, existing copper-tungsten contact materials and their connection processes are no longer adequate to meet the extreme operating conditions of breaking 80kA high short-circuit currents, and breakthroughs in material systems and preparation processes are urgently needed. Summary of the Invention

[0006] The purpose of this invention is to solve the problems of insufficient arc erosion resistance and poor connection reliability between copper-tungsten contacts and conductive rods in the prior art.

[0007] The objective of this invention is achieved through the following technical solution: A copper-tungsten contact material, comprising, by weight percentage, 75-85% tungsten, 0.3-0.8% multi-component composite additives, and the balance being copper; The multi-component composite additive includes cobalt, nickel, and lanthanum oxide, and the mass ratio of cobalt, nickel, and lanthanum oxide is 1-2:0.5-1:1. Preferably, in the microstructure of the copper-tungsten contact material, the tungsten particles are polygonal and interconnected to form a continuous skeleton, the copper phase is uniformly filled in the gaps between the tungsten skeleton, and the average size of the tungsten grains is 3-8 μm.

[0008] Preferably, the density of the copper-tungsten contact material is ≥99.2%.

[0009] Preferably, the contact material has an electrical conductivity ≥42% IACS, a bending strength ≥1400MPa, and a hardness ≥250HB.

[0010] Based on the same inventive concept, the present invention also provides a method for preparing a copper-tungsten contact material, the method comprising the following steps: Tungsten powder with a Fisher particle size of 2-5 μm and a multi-component composite additive are ball-milled in a certain proportion to obtain a mixed powder; wherein, based on the mass percentage of the mixed powder, tungsten powder accounts for 75-85%, multi-component composite additive accounts for 0.3-0.8%, and the balance is copper powder; The mixed powder is cold-pressed to obtain a skeleton compact; The skeleton compact is pre-sintered at high temperature in a hydrogen atmosphere to obtain a sintered skeleton. Oxygen-free copper is placed above the sintered skeleton, heated in a vacuum furnace and subjected to pressure melting and infiltration, and then cooled to obtain the copper-tungsten contact material as described above.

[0011] Preferably, the ball-to-material ratio of the high-energy ball mill is 5:1-8:1, the milling time is 10-20 hours, and the rotation speed is 200-300 rpm.

[0012] Preferably, the high-temperature pre-sintering temperature is 1300-1500℃, the heating rate is 5-10℃ / min, and the holding time is 3-5h.

[0013] Preferably, the pressure infiltration temperature is 1400-1550℃, and the vacuum degree is ≤5×10⁻⁶. - Apply pressure of 5-10 MPa and maintain the temperature for 2-4 hours.

[0014] Based on the same inventive concept, the present invention also provides a contact, including a contact body and a conductive rod, characterized in that the contact body is made of the copper-tungsten contact material described above.

[0015] Preferably, the conductive rod is made of copper-chromium-zirconium alloy.

[0016] Preferably, the surface of the conductive rod to be welded has Ra ≤ 1.6 μm.

[0017] Preferably, the copper-chromium-zirconium alloy comprises, by weight percentage: 0.5-1.2% chromium, 0.08-0.3% zirconium, and the balance being copper.

[0018] Based on the same inventive concept, the present invention also provides a method for preparing the contact, characterized in that the method includes the following steps: The contact body and the conductive rod are vacuum diffusion welded together to form an integral contact. The integral contact is subjected to solution aging treatment.

[0019] Preferably, the vacuum diffusion welding temperature is 950-1050℃, the pressure is 10-25MPa, and the holding time is 1-3h.

[0020] Preferably, the solution aging treatment includes: solution treatment at 980-1020℃ for 1-2 hours followed by water quenching, and aging at 470-500℃ for 3-5 hours.

[0021] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention achieves a breakthrough improvement in the comprehensive performance of copper-tungsten contact materials under extreme 800kV 80kA conditions through synergistic innovation in composition optimization, structural design, and process improvement. Firstly, a multi-component composite additive composed of cobalt, nickel, and lanthanum oxide in a specific ratio is introduced into the contact body. The principle is that cobalt and nickel can undergo micro-alloying with tungsten and copper during high-temperature sintering, significantly improving the wettability between tungsten and copper, allowing molten copper to more fully fill the gaps in the tungsten skeleton, thereby greatly increasing the bonding strength of the tungsten-copper interface. Simultaneously, lanthanum oxide, as a dispersed reinforcing phase, can effectively pin tungsten grain boundaries, inhibiting abnormal grain growth and high-temperature creep at high temperatures. Based on this principle, this composition design increases the material density to over 99.2%, eliminates internal micropores, effectively avoids localized preferential breakdown under arcing, refines the grains, and significantly enhances the material's resistance to melting and splashing under 80kA high-energy arc impact, greatly reducing the ablation depth and effectively preventing contact contour deformation and electric field distortion.

[0022] Secondly, in terms of microstructure, the synergy between additives and high-energy ball milling and pressure infiltration processes enables the contact body to form a continuous skeleton structure with interconnected tungsten particles and a grain size controlled at 3-8 μm, with the copper phase uniformly filling the gaps. This structure utilizes the high arc resistance of the tungsten skeleton and achieves high conductivity through the copper phase. Combined with the fine-grain strengthening effect, the bending strength of the material jumps to over 1400 MPa and the hardness exceeds 250 HB, overcoming the brittleness of traditional high-tungsten materials and achieving a good match between ablation resistance and mechanical properties.

[0023] Finally, regarding the connection structure, this invention employs high-temperature diffusion welding instead of traditional brazing. The principle is that under high temperature and pressure, atoms at the interface between the copper-tungsten contact body and the copper-chromium-zirconium conductive rod undergo mutual diffusion, forming an atomic-level metallurgical bonding layer, eliminating the abrupt compositional changes at the interface of traditional welds. Combined with subsequent solution-aging heat treatment, this not only strengthens the conductive rod substrate but also eliminates residual welding stress. This improvement completely solves the interface cracking problem caused by the mismatch in thermal expansion coefficients in traditional layered contacts, resulting in an interface shear strength exceeding 280 MPa. It achieves a continuous transition between electrical and thermal conductivity, avoiding localized overheating caused by excessively high interface resistance, and fundamentally ensuring the overall structural reliability and long service life of the contact under extreme high-current impacts. Detailed Implementation

[0024] The technical solution will be further described below with reference to specific embodiments to help understand the content of the present invention.

[0025] Example 1 A copper-tungsten contact material, comprising, by weight percentage, 75-85% tungsten, 0.3-0.8% multi-component composite additives, and the balance being copper; The multi-component composite additive includes cobalt, nickel, and lanthanum oxide, and the mass ratio of cobalt, nickel, and lanthanum oxide is 1-2:0.5-1:1. Preferably, in the microstructure of the copper-tungsten contact material, the tungsten particles are polygonal and interconnected to form a continuous skeleton, the copper phase is uniformly filled in the gaps between the tungsten skeleton, and the average size of the tungsten grains is 3-8 μm.

[0026] Preferably, the density of the copper-tungsten contact material is ≥99.2%.

[0027] Preferably, the contact material has an electrical conductivity ≥42% IACS, a bending strength ≥1400MPa, and a hardness ≥250HB.

[0028] This invention provides a high-strength, highly dense, and reliable copper-tungsten contact material for 800kV 80kA circuit breakers and its preparation method by introducing multi-component composite additives to optimize the contact body composition, improving the melting and infiltration process, and employing diffusion welding composite technology. The specific technical solution is as follows: The core technological improvements of the copper-tungsten contact material for 800kV 80kA circuit breakers of this invention lie in the optimization of composition, structural design, and improvement of the manufacturing process.

[0029] This invention optimizes the composition of the contact: the contact body is a copper-tungsten alloy composite material, wherein the mass percentage of tungsten is 75-85%, the mass percentage of copper is 15-25%, and a multi-component composite additive is added, accounting for 0.3-0.8% of the total amount; the conductive rod is a copper-chromium-zirconium alloy, wherein the mass percentage of chromium is 0.5-1.2%, the mass percentage of zirconium is 0.08-0.3%, and the balance is copper. The multi-component composite additive is composed of oxides of cobalt (Co), nickel (Ni), and lanthanum (La2O3), with a mass ratio of Co:Ni:La2O3=1-2:0.5-1:1. The core function of this additive is that Co and Ni can undergo micro-alloying with W and Cu during high-temperature sintering, improving the wettability of W and Cu and significantly increasing the bonding strength of the W-Cu interface; La2O3, as a dispersed strengthening phase, can pin tungsten grain boundaries, inhibit tungsten grain growth and high-temperature creep, and greatly improve the material's resistance to arc erosion.

[0030] This invention employs an innovative microstructure design: in the microstructure of the contact body, tungsten particles are polygonal and interconnected to form a continuous skeleton, with copper phase uniformly filling the gaps in the tungsten skeleton. The average size of the tungsten grains is 3-8 μm. This structure can utilize both the high arc resistance of the tungsten skeleton and the high conductivity of the copper phase to achieve a balance between arc resistance and conductivity. At the same time, the contact body has a density ≥99.2%, conductivity ≥42%IACS, bending strength ≥1400MPa, and hardness ≥250HB. The high density eliminates internal porosity and avoids local breakdown under the action of electric arc.

[0031] Example 2 Based on the same inventive concept, the present invention also provides a method for preparing a copper-tungsten contact material, the method comprising the following steps: Tungsten powder with a Fisher particle size of 2-5 μm and a multi-component composite additive are ball-milled in a certain proportion to obtain a mixed powder; wherein, based on the mass percentage of the mixed powder, tungsten powder accounts for 75-85%, multi-component composite additive accounts for 0.3-0.8%, and the balance is copper powder; The mixed powder is cold-pressed to obtain a skeleton compact; The skeleton compact is pre-sintered at high temperature in a hydrogen atmosphere to obtain a sintered skeleton. Oxygen-free copper is placed above the sintered skeleton, heated in a vacuum furnace and subjected to pressure melting and infiltration, and then cooled to obtain the copper-tungsten contact material as described above.

[0032] Preferably, the ball-to-material ratio of the high-energy ball mill is 5:1-8:1, the milling time is 10-20 hours, and the rotation speed is 200-300 rpm.

[0033] Preferably, the high-temperature pre-sintering temperature is 1300-1500℃, the heating rate is 5-10℃ / min, and the holding time is 3-5h.

[0034] Preferably, the pressure infiltration temperature is 1400-1550℃, and the vacuum degree is ≤5×10⁻⁶. - Apply pressure of 5-10 MPa and maintain the temperature for 2-4 hours.

[0035] The specific implementation process includes the following steps: (1) Raw material preparation: Tungsten powder with a Fisher particle size of 2-5 μm and multi-component composite additives are loaded into a ball mill for high-energy ball milling in a certain proportion. The ball-to-material ratio is 5:1-8:1, the ball milling time is 10-20 h, and the rotation speed is 200-300 rpm. High-energy ball milling makes the additives uniformly dispersed and refined the tungsten powder.

[0036] (2) Press molding: The above mixed powder is loaded into the contact mold and cold-pressed under a pressure of 150-250MPa to obtain the skeleton blank.

[0037] (3) High-temperature pre-sintering: The skeleton compact is pre-sintered at 1300-1500℃ in a hydrogen atmosphere, with a heating rate of 5-10℃ / min and a holding time of 3-5h. This step removes impurities and forms sintering necks between tungsten particles to obtain a high-strength sintered skeleton.

[0038] (4) Melting and infiltration: Place oxygen-free copper above the sintering skeleton and heat it in a vacuum furnace to 1400-1550℃, with a vacuum degree ≤5×10 - ³Pa, pressurized to 5-10MPa, and held at the temperature for 2-4 hours. During the melting and infiltration process, pressurized filling is used to ensure that the copper liquid fully fills the pores of the tungsten skeleton under the combined action of capillary force and external pressure. After cooling, a high-density copper-tungsten contact body is obtained.

[0039] Example 3 Based on the same inventive concept, the present invention also provides a contact, including a contact body and a conductive rod, characterized in that the contact body is made of the copper-tungsten contact material described above.

[0040] Preferably, the conductive rod is made of copper-chromium-zirconium alloy.

[0041] Preferably, the surface of the conductive rod to be welded has Ra ≤ 1.6 μm.

[0042] Preferably, the copper-chromium-zirconium alloy comprises, by weight percentage: 0.5-1.2% chromium, 0.08-0.3% zirconium, and the balance being copper.

[0043] Example 4 Based on the same inventive concept, the present invention also provides a method for preparing the contact, characterized in that the method includes the following steps: The contact body and the conductive rod are vacuum diffusion welded together to form an integral contact. The integral contact is subjected to solution aging treatment.

[0044] Preferably, the vacuum diffusion welding temperature is 950-1050℃, the pressure is 10-25MPa, and the holding time is 1-3h.

[0045] Preferably, the solution aging treatment includes: solution treatment at 980-1020℃ for 1-2 hours followed by water quenching, and aging at 470-500℃ for 3-5 hours.

[0046] The vacuum diffusion welding process includes: machining the surface of the chromium-zirconium copper conductive rod to be welded to Ra≤1.6μm, aligning it with the surface of the copper-tungsten contact body to be welded, placing it in a vacuum diffusion welding furnace, and holding it at 950-1050℃ and 10-25MPa pressure for 1-3 hours. Under these conditions, atoms at the interface undergo interdiffusion, forming a strong metallurgical bonding layer with a bonding strength higher than that of the base material.

[0047] The heat treatment includes: solution aging treatment of the welded integral contact (solution at 980-1020℃ for 1-2 hours followed by water quenching, and aging at 470-500℃ for 3-5 hours) to achieve the best strengthening effect for the conductive rod and eliminate welding stress.

[0048] Finally, it is machined to the finished size according to requirements.

[0049] The contact body and the conductive rod are bonded together by high-temperature diffusion welding to form a metallurgical interface, which replaces the traditional brazing method and achieves a strong connection at the atomic level, solving the problems of high resistance and easy cracking of traditional welding interfaces.

[0050] Example 5 (1) Raw material preparation: Tungsten powder with a Fisher particle size of 3μm was selected. The mixture was prepared according to the following mass percentages: W 82%, Cu 17.5% (reserve for melting and infiltration), Co 0.25%, Ni 0.15%, and La2O3 0.1%. The above powder was loaded into a ball mill with a ball-to-powder ratio of 6:1, a rotation speed of 250rpm, and ball milled for 15h.

[0051] (2) Skeleton forming: The mixture is loaded into the contact mold and cold-pressed under a pressure of 200MPa to obtain a skeleton blank of φ60mm×30mm.

[0052] (3) Pre-sintering: Place the skeleton compact in a hydrogen sintering furnace, heat it to 1400℃ at 8℃ / min, hold it for 4h, and then cool it with the furnace.

[0053] (4) Melting and infiltration: Place the oxygen-free copper block on top of the sintered tungsten skeleton, put it into a vacuum sintering furnace, and evacuate to 3×10 - The temperature was increased to 1480℃ and held for 3 hours, with a micro-pressure of 5MPa applied during the filling process. After cooling in the furnace, the copper-tungsten contact body was obtained.

[0054] (5) Diffusion welding: The chromium zirconium copper rod (Cr 0.8%, Zr 0.15%) is machined to match the dimensions of the contact body, and the surface to be welded is ground smooth. The two are butt-jointed and placed in a vacuum diffusion welding furnace and held at 1000℃ and 20MPa pressure for 2 hours.

[0055] (6) Heat treatment and machining: After welding, the contacts are solution treated at 1000℃ for 1.5h, then water quenched, and then aged at 480℃ for 4h. Finally, they are turned and ground according to the drawings to the finished product.

[0056] Testing revealed that the contact body of this embodiment has a density of 99.5%, an electrical conductivity of 45% IACS, a bending strength of 1520 MPa, and a hardness of 268 HB. The shear strength at the diffusion weld interface is 280 MPa.

[0057] Example 6 In this embodiment, the composition of the contact body was adjusted to 78% W, 21.3% Cu, 0.3% Co, 0.2% Ni, and 0.2% La2O3, with the remaining process conditions the same as in Example 5.

[0058] Tests showed that the contact body has a density of 99.3%, an electrical conductivity of 48% IACS, a bending strength of 1430 MPa, and a hardness of 255 HB.

[0059] Example 7 This embodiment aims to verify the performance when a lower tungsten content is combined with an optimized additive ratio.

[0060] (1) Raw material preparation: Tungsten powder with a Fisher particle size of 4μm was selected. The mixture was prepared according to the following mass percentages: W 76%, Cu 23.2% (reserve for melting and infiltration), Co 0.3%, Ni 0.3%, La2O3 0.2%. The above powder was loaded into a ball mill with a ball-to-powder ratio of 7:1, a rotation speed of 280rpm, and ball milled for 18h.

[0061] (2) Skeleton forming: Cold pressing is performed under 180MPa pressure to obtain a skeleton blank with a diameter of φ60mm×30mm.

[0062] (3) Pre-sintering: In a hydrogen atmosphere, the temperature is increased to 1350℃ at 10℃ / min and held for 5 hours.

[0063] (4) Melting and infiltration: Vacuum degree 4×10 - ³Pa, heat to 1420℃, hold for 3.5 hours, and apply 8MPa micro-pressure to assist filling during the process.

[0064] (5) Diffusion welding: The composition of the chromium zirconium copper handle is the same as in Example 5. The welding temperature is 980℃, the pressure is 18MPa, and the heat preservation time is 2.5h.

[0065] (6) Heat treatment and machining: solution treatment at 990℃ for 1.8h followed by water quenching, aging at 490℃ for 4h, and then machining.

[0066] Testing revealed that the contact body of this embodiment has a density of 99.4%, an electrical conductivity of 50% IACS, a bending strength of 1380 MPa, and a hardness of 248 HB. The shear strength at the diffusion weld interface is 275 MPa.

[0067] Example 8 This embodiment uses a high tungsten content and additive ratio to verify the ultimate ablation resistance performance.

[0068] (1) Raw material preparation: Tungsten powder with a Fisher particle size of 2.5 μm was selected. The mixture was prepared according to the following mass percentages: W 84%, Cu 15.2%, Co 0.4%, Ni 0.2%, La2O3 0.2%. Ball milling process: ball-to-material ratio 8:1, rotation speed 300 rpm, ball milling for 20 hours.

[0069] (2) Skeleton forming: Cold pressing under 250MPa pressure.

[0070] (3) Pre-sintering: In a hydrogen atmosphere, the temperature is increased to 1480℃ at 6℃ / min and held for 3h.

[0071] (4) Melting and infiltration: vacuum degree 2×10 - Heat to 1530℃, hold for 2 hours, and pressurize to 10MPa.

[0072] (5) Diffusion welding: The composition of the chromium zirconium copper handle is the same as in Example 5. The welding temperature is 1020℃, the pressure is 22MPa, and the heat preservation time is 1.5h.

[0073] (6) Heat treatment and machining: solution heat treatment at 1010℃ for 1.2h followed by water quenching, and aging at 475℃ for 5h.

[0074] Testing revealed that the contact body of this embodiment has a density of 99.6%, an electrical conductivity of 43% IACS, a bending strength of 1580 MPa, and a hardness of 285 HB. The shear strength at the diffusion weld interface is 290 MPa.

[0075] Example 9 In this embodiment, the ratio of the multi-component composite additive was adjusted to Co:Ni:La2O3=2:1:1 to verify the effect of different ratios on performance.

[0076] (1) Raw material preparation: W 80%, Cu 19.4%, Co 0.4%, Ni 0.2%, La2O3 0.2%. Tungsten powder particle size 3μm, ball milling parameters are the same as in Example 5.

[0077] (2) Skeleton forming: 200MPa pressure.

[0078] (3) Pre-sintering: 1400℃, 4 hours.

[0079] (4) Melting and infiltration: 1480℃, 3 hours, vacuum degree 5×10 - ³ Pa, pressurized to 5 MPa.

[0080] (5) Diffusion welding: welding temperature 1000℃, pressure 20MPa, heat preservation for 2 hours.

[0081] (6) Heat treatment and machining: Same as in Example 5.

[0082] Testing revealed that the contact body of this embodiment has a density of 99.3%, an electrical conductivity of 46% IACS, a bending strength of 1490 MPa, and a hardness of 262 HB. The shear strength at the diffusion weld interface is 285 MPa.

[0083] Example 10 (Verifying the minimum / maximum endpoints of each parameter range) (1) Raw material preparation: Tungsten powder with a Fisher particle size of 2μm was selected. The mixture was prepared according to the following mass percentages: W 75%, Cu 24.7% (reserve for melting and infiltration), Co 0.12%, Ni 0.06%, La2O3 0.12% (i.e., total additives 0.3%, Co:Ni:La2O3=1:0.5:1). The above powder was loaded into a ball mill with a ball-to-powder ratio of 5:1, a rotation speed of 200rpm, and ball milled for 10h.

[0084] (2) Skeleton forming: The mixture is loaded into the contact mold and cold-pressed under a pressure of 150MPa to obtain the skeleton blank.

[0085] (3) Pre-sintering: Place the skeleton compact in a hydrogen sintering furnace, heat it to 1300℃ at 5℃ / min, hold it for 3h, and then cool it with the furnace.

[0086] (4) Melting and infiltration: Place the oxygen-free copper block on top of the sintered tungsten skeleton, put it into a vacuum sintering furnace, and evacuate to 5×10 - The temperature was increased to 1400℃ and held for 2 hours, with a micro-pressure of 5MPa applied during the filling process. After cooling in the furnace, the copper-tungsten contact body was obtained.

[0087] (5) Diffusion welding: The chromium zirconium copper rod (Cr 0.5%, Zr 0.08%) is processed to match the dimensions of the contact body, and the surface to be welded is ground smooth to Ra≤1.6μm. The two are butt-jointed and placed in a vacuum diffusion welding furnace and held at 950℃ and 10MPa pressure for 1h.

[0088] (6) Heat treatment and machining: After welding, the contacts are solution treated at 980℃ for 1 hour, then water quenched, and then aged at 470℃ for 3 hours. Finally, they are turned and ground according to the drawings to the finished product.

[0089] Testing revealed that the contact body of this embodiment has a density of 99.2%, an electrical conductivity of 52% IACS, a bending strength of 1400 MPa, and a hardness of 250 HB. The shear strength at the diffusion weld interface is 260 MPa.

[0090] Example 11 (Verifying the maximum / maximum endpoints of each parameter range) (1) Raw material preparation: Tungsten powder with a Fisher particle size of 5 μm was selected. The mixture was prepared according to the following mass percentages: W 85%, Cu 14.2% (reserve for melting and infiltration), Co 0.4%, Ni 0.2%, La2O3 0.2% (i.e., total additives 0.8%, Co:Ni:La2O3=2:1:1). The above powder was loaded into a ball mill with a ball-to-powder ratio of 8:1, a rotation speed of 300 rpm, and ball milled for 20 h.

[0091] (2) Skeleton forming: The mixture is loaded into the contact mold and cold-pressed under a pressure of 250MPa to obtain the skeleton blank.

[0092] (3) Pre-sintering: Place the skeleton compact in a hydrogen sintering furnace, heat it to 1500℃ at 10℃ / min, hold it for 5 hours, and then cool it with the furnace.

[0093] (4) Melting and infiltration: Place the oxygen-free copper block on top of the sintered tungsten skeleton, put it into a vacuum sintering furnace, and evacuate to 1×10⁻⁶. - The temperature was increased to 1550℃ and held for 4 hours, with a micro-pressure of 10MPa applied during the filling process. After cooling in the furnace, the copper-tungsten contact body was obtained.

[0094] (5) Diffusion welding: The chromium zirconium copper rod (Cr 1.2%, Zr 0.3%) is machined to match the dimensions of the contact body, and the surface to be welded is ground smooth to Ra≤1.6μm. The two are butt-jointed and placed in a vacuum diffusion welding furnace and held at 1050℃ and 25MPa pressure for 3h.

[0095] (6) Heat treatment and machining: After welding, the contacts are solution treated at 1020℃ for 2 hours, then water quenched, and then aged at 500℃ for 5 hours. Finally, they are turned and ground according to the drawings to the finished product.

[0096] Testing revealed that the contact body of this embodiment has a density of 99.6%, an electrical conductivity of 42% IACS, a bending strength of 1600 MPa, and a hardness of 295 HB. The shear strength at the diffusion weld interface is 295 MPa.

[0097] Example 12 (Verifying the midpoints of the parameter ranges) (1) Raw material preparation: Tungsten powder with a Fisher particle size of 3.5 μm was selected. The mixture was prepared according to the following mass percentages: W 80%, Cu 19.45% (reserve for melting and infiltration), Co 0.254%, Ni 0.127%, La2O3 0.169% (i.e., total additives 0.55%, Co:Ni:La2O3=1.5:0.75:1). The above powder was loaded into a ball mill with a ball-to-powder ratio of 6.5:1, a rotation speed of 250 rpm, and ball milled for 15 h.

[0098] (2) Skeleton forming: The mixture is loaded into the contact mold and cold-pressed under a pressure of 200MPa to obtain the skeleton blank.

[0099] (3) Pre-sintering: The skeleton compact is placed in a hydrogen sintering furnace and heated to 1400℃ at 7.5℃ / min, held for 4 hours, and then cooled with the furnace.

[0100] (4) Melting and infiltration: Place the oxygen-free copper block on top of the sintered tungsten skeleton, put it into a vacuum sintering furnace, and evacuate to 3×10 - The temperature was increased to 1475℃ and held for 3 hours, during which a micro-pressure of 7.5 MPa was applied to assist filling. After cooling in the furnace, the copper-tungsten contact body was obtained.

[0101] (5) Diffusion welding: The chromium zirconium copper rod (Cr 0.85%, Zr 0.19%) is processed to match the dimensions of the contact body, and the surface to be welded is ground smooth to Ra≤1.6μm. The two are butt-jointed and placed in a vacuum diffusion welding furnace and held at 1000℃ and 17.5MPa pressure for 2h.

[0102] (6) Heat treatment and machining: After welding, the contacts are solution treated at 1000℃ for 1.5h, then water quenched, and then aged at 485℃ for 4h. Finally, they are turned and ground according to the drawings to the finished product.

[0103] Testing revealed that the contact body of this embodiment has a density of 99.4%, an electrical conductivity of 47% IACS, a bending strength of 1480 MPa, and a hardness of 262 HB. The shear strength at the diffusion weld interface is 282 MPa.

[0104] Example 13 (Verification of the second smallest endpoint of low tungsten content combined with intermediate parameters) (1) Raw material preparation: Tungsten powder with a Fisher particle size of 4 μm was selected. The mixture was prepared according to the following mass percentages: W 77%, Cu 22.6% (reserve for melting and infiltration), Co 0.133%, Ni 0.133%, La2O3 0.133% (i.e., total additives 0.4%, Co:Ni:La2O3=1:1:1). The above powder was loaded into a ball mill with a ball-to-powder ratio of 6:1, a rotation speed of 220 rpm, and ball milled for 12 h.

[0105] (2) Skeleton forming: The mixture is loaded into the contact mold and cold-pressed under a pressure of 190MPa to obtain the skeleton blank.

[0106] (3) Pre-sintering: The skeleton compact is placed in a hydrogen sintering furnace and heated to 1350℃ at 6℃ / min, held for 4.5h, and then cooled with the furnace.

[0107] (4) Melting and infiltration: Place the oxygen-free copper block on top of the sintered tungsten skeleton, put it into a vacuum sintering furnace, and evacuate to 2×10⁻⁶. - The temperature was increased to 1450℃ and held for 3.5 hours, with a micro-pressure of 6MPa applied during the filling process. After furnace cooling, the copper-tungsten contact body was obtained.

[0108] (5) Diffusion welding: The chromium zirconium copper rod (Cr 0.6%, Zr 0.1%) is machined to match the dimensions of the contact body, and the surface to be welded is ground smooth to Ra≤1.6μm. The two are butt-jointed and placed in a vacuum diffusion welding furnace and held at 970℃ and 12MPa pressure for 2.2h.

[0109] (6) Heat treatment and machining: After welding, the contacts are solution treated at 985℃ for 1.2h, then water quenched, and then aged at 475℃ for 3.5h. Finally, they are turned and ground according to the drawings to the finished product.

[0110] Testing revealed that the contact body of this embodiment has a density of 99.3%, an electrical conductivity of 50% IACS, a bending strength of 1420 MPa, and a hardness of 252 HB. The shear strength at the diffusion weld interface is 268 MPa.

[0111] Example 14 (Verification of the second-largest endpoint of the combination of high tungsten content and intermediate parameters) (1) Raw material preparation: Tungsten powder with a Fisher particle size of 2.5 μm was selected. The mixture was prepared according to the following mass percentages: W 83%, Cu 16.4% (reserve for melting and infiltration), Co 0.343%, Ni 0.086%, La2O3 0.171% (i.e., total additives 0.6%, Co:Ni:La2O3=2:0.5:1). The above powder was loaded into a ball mill with a ball-to-powder ratio of 7:1, a rotation speed of 280 rpm, and ball milled for 18 h.

[0112] (2) Skeleton forming: The mixture is loaded into the contact mold and cold-pressed under a pressure of 220MPa to obtain the skeleton blank.

[0113] (3) Pre-sintering: The skeleton compact is placed in a hydrogen sintering furnace, heated to 1450℃ at 9℃ / min, held for 3.5h, and then cooled with the furnace.

[0114] (4) Melting and infiltration: Place the oxygen-free copper block on top of the sintered tungsten skeleton, put it into a vacuum sintering furnace, and evacuate to 4×10 - The temperature was increased to 1500℃ and held for 2.5 hours, with a micro-pressure of 9MPa applied during the filling process. After cooling in the furnace, the copper-tungsten contact body was obtained.

[0115] (5) Diffusion welding: The chromium zirconium copper rod (Cr 1.0%, Zr 0.25%) is processed to match the dimensions of the contact body, and the surface to be welded is ground smooth to Ra≤1.6μm. The two are butt-jointed and placed in a vacuum diffusion welding furnace and held at 1030℃ and 23MPa pressure for 1.8h.

[0116] (6) Heat treatment and machining: After welding, the contacts are solution treated at 1015℃ for 1.8h, then water quenched, and then aged at 495℃ for 4.5h. Finally, they are turned and ground according to the drawings to the finished product.

[0117] Testing revealed that the contact body of this embodiment has a density of 99.5%, an electrical conductivity of 44% IACS, a bending strength of 1550 MPa, and a hardness of 278 HB. The shear strength at the diffusion weld interface is 288 MPa.

[0118] Comparative Example 1 Conventional CuW80 material (without multi-component additives) was used and connected to a chromium-zirconium-copper shank via silver brazing. After a simulated 80kA arc ablation test, the ablation depth of Comparative Example 1 was 2.5mm, while that of Example 5 was 1.6mm, a reduction of 36%. After thermal cycling tests, microcracks appeared at the brazed interface of Comparative Example 1, while the interface of Example 5 remained intact.

[0119] Comparative Example 2 This comparative example uses the same tungsten content (82%) as Example 5, but without the addition of multi-component composite additives (Co, Ni, La2O3). The rest of the process is the same, in order to verify the effect of the additives.

[0120] Testing revealed that the contact body of Comparative Example 2 had a density of 98.5% (slightly lower due to the lack of additive-activated sintering), an electrical conductivity of 41% IACS, a flexural strength of 1150 MPa, and a hardness of 225 HB. The shear strength at the diffusion weld interface was 210 MPa (interfacial bonding was slightly poor). After a simulated 80 kA arc ablation test, the ablation depth was 2.3 mm, significantly higher than the 1.6 mm in Example 5.

[0121]

[0122] The core of this invention lies in addressing the performance bottleneck of existing copper-tungsten contact materials under extreme operating conditions of 800kV 80kA. Through synergistic innovation of "composition optimization + structural design + process improvement", a breakthrough improvement in the comprehensive performance of the contact materials is achieved, meeting the requirements for use in ultra-high voltage circuit breakers.

[0123] The contact material of this invention features a unique copper-tungsten composition ratio (75-85% tungsten, 15-25% copper) and a core design of multi-component composite additives—composed of cobalt (Co), nickel (Ni), and lanthanum oxide (La2O3), with the mass ratio of the three controlled at 1-2:0.5-1:1, and the additive amount accounting for 0.3-0.8% of the total material. This composition design is the core of improving the material's arc erosion resistance, W-Cu interfacial bonding strength, and density, and is also one of the core differences between this invention and existing technologies.

[0124] The contact of this invention adopts a composite structure design, namely, the contact body is a copper-tungsten alloy composite material, the conductive rod is a copper-chromium-zirconium alloy combined structure, and the two are connected by high-temperature diffusion welding to form a metallurgical interface. This structural design completely solves the problems of interface defects, high resistance, and easy cracking in traditional brazing connections, and is the key to ensuring structural reliability.

[0125] This invention provides an innovative contact material preparation process and key parameters, specifically including high-energy ball milling (ball-to-material ratio 5:1-8:1, rotation speed 200-300 rpm, time 10-20 h), high-temperature pre-calcination (hydrogen atmosphere, 1300-1500℃, heating rate 5-10℃ / min, holding time 3-5 h), and pressure melting infiltration (vacuum degree ≤5×10). - The process involves heat treatment at 1400-1550℃ for 2-4 hours, including methods such as vacuum diffusion welding (950-1050℃, 10-25MPa, 1-3 hours) and solution aging heat treatment (980-1020℃ for 1-2 hours followed by water quenching and aging at 470-500℃ for 3-5 hours). The coordinated control of these process parameters is crucial for achieving high density and excellent mechanical and electrical properties in the material.

[0126] The key performance indicators of the contact body of this invention are significantly different from those of the prior art, namely, density ≥99.2%, conductivity ≥42%IACS, bending strength ≥1400MPa, and hardness ≥250HB. At the same time, the protective material exhibits excellent performance under 80kA arc erosion conditions (ablation depth and mass loss rate are significantly better than traditional copper-tungsten materials). These performance indicators directly meet the extreme operating conditions of 1100kV 80kA UHV circuit breakers and are the core embodiment of the technical effect of this invention.

[0127] The contact material of this invention exhibits excellent resistance to arc erosion, with an ablation depth that is 36% lower than that of traditional materials. This is mainly attributed to the synergistic effect of optimized composition, microstructure design, and interface connection method.

[0128] First, the introduction of multi-component composite additives fundamentally enhances the intrinsic ablation resistance of the material. Cobalt and nickel undergo microalloying with tungsten and copper during high-temperature sintering, significantly improving the wettability of the tungsten-copper two-phase system and greatly strengthening the W-Cu interfacial bonding strength. This effectively suppresses preferential cracking and material spalling caused by weak interfacial bonding under arc impact. At the same time, lanthanum oxide (La2O3), as a dispersed reinforcing phase, can effectively pin tungsten grain boundaries, inhibiting grain growth and creep behavior at high temperatures, further endowing the material with excellent resistance to arc erosion.

[0129] Secondly, at the microstructure and density level, the refining effect of the composite additives promotes the formation of an ideal microstructure in the contact body: "polygonal tungsten particles interconnected to form a continuous skeleton, with copper phase uniformly filling the gaps in the skeleton." This structure fully utilizes the high arc resistance of the continuous tungsten skeleton and achieves rapid heat dissipation from the arc through the uniformly distributed copper phase, achieving an optimal match between arc resistance and conductivity. Furthermore, this invention, through the synergistic process of activated sintering and pressurized melting infiltration, increases the material density to over 99.5%, virtually eliminating internal micropores. Since residual gas inside the pores easily expands under the high temperature of the arc, causing preferential local breakdown, the ultra-high density fundamentally eliminates this cause of localized ablation, allowing arc energy to be dissipated uniformly rather than concentrated in localized areas.

[0130] Finally, the innovative design of the contact interface also plays a crucial role in improving the overall ablation performance. Traditional silver brazing interfaces have inherent defects such as high resistance and susceptibility to microcracks during thermal cycling, which easily lead to localized overheating and electric field distortion under high current impact, thereby exacerbating localized contact ablation. This invention uses high-temperature vacuum diffusion welding to replace traditional brazing, forming an atomic-level metallurgical bond between the copper-tungsten contact body and the chromium-zirconium-copper conductive rod. The interface bonding strength is high and free of microcrack defects, achieving a continuous and smooth transition between electrical and thermal conductivity. This not only completely avoids localized overheating caused by high interface resistance but also eliminates arc-concentrated ablation induced by electric field distortion, thus ensuring the overall structural integrity and low ablation rate of the contact under extreme high current conditions.

[0131] This invention achieves a comprehensive improvement over existing technologies through component optimization, structural design, and process improvements. Specific effects are shown below, all supported by experimental data, and demonstrate a clear contrast with existing technologies: (1) Ultra-high ablation resistance: The introduction of multi-component composite additives refines the grains and strengthens the W-Cu interface, significantly improving the material's resistance to arc ablation. Verified by a simulated 80kA arc ablation test, the ablation depth of the contact material of the present invention is reduced by 36% compared with the traditional CuW material (Comparative Example 1) (ablation depth of 1.6mm in Example 5 and 2.5mm in Comparative Example 1), and the mass loss rate is reduced by more than 20% compared with the traditional CuW material, effectively avoiding contact contour deformation and electric field distortion.

[0132] (2) High overall structural reliability: High-temperature diffusion welding is used instead of traditional brazing, eliminating welding interface defects and significantly improving interface bonding strength. In Example 5, the shear strength of the diffusion weld interface reached 280 MPa, while the shear strength of the interface in Comparative Example 2 without additives was only 210 MPa. After thermal cycling test, microcracks appeared at the interface of the traditional brazing (Comparative Example 1), while the diffusion weld interface of the present invention remained intact and had no risk of cracking under high current impact. The electrical and thermal conductivity achieved a continuous transition, avoiding local overheating caused by excessively high interface resistance.

[0133] (3) The material has extremely high density: Through the “activation sintering + pressure melting and infiltration” process, the material density reaches more than 99.2% (99.5% for Example 5 and 99.6% for Example 4), with almost no micropores, effectively suppressing local preferential ablation under the action of electric arc; while the comparative example 2 without the addition of multi-component additives has a density of only 98.5%, with a small number of pores, which is prone to local breakdown.

[0134] (4) Excellent comprehensive mechanical and electrical properties: The contact body and the conductive rod have undergone composition optimization and heat treatment, achieving a good match between high strength and high conductivity. In Example 5, the contact body has a conductivity of 45% IACS, a bending strength of 1520MPa, and a hardness of 268HB; in Example 3, the conductivity reaches 50% IACS and the bending strength is 1380MPa, both of which meet the mechanical and electrical requirements of the contact material under the extreme working condition of 1100kV 80kA; while the comparative example 2 without additives has a bending strength of only 1150MPa, a hardness of 225HB, and a conductivity of 41% IACS, and its comprehensive performance is significantly inferior to that of the present invention.

[0135] (5) Extended service life: It solves the problem of interface cracks caused by the mismatch of thermal expansion coefficients of traditional layered contacts. Combined with the improvement of ablation resistance and connection reliability, it greatly extends the service life of the contacts and reduces the maintenance cost and operation risk of UHV circuit breakers.

[0136] The above are merely embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention are included within the scope of the claims of the present invention.

Claims

1. A copper-tungsten contact material, characterized in that, By mass percentage, it includes 75-85% tungsten, 0.3-0.8% multi-component composite additives, and the balance is copper; The multi-component composite additive includes cobalt, nickel, and lanthanum oxide, and the mass ratio of cobalt, nickel, and lanthanum oxide is 1-2:0.5-1:

1.

2. The copper-tungsten contact material as described in claim 1, characterized in that, In the microstructure of the copper-tungsten contact material, the tungsten particles are polygonal and interconnected to form a continuous skeleton, and the copper phase is uniformly filled in the gaps between the tungsten skeleton. The average size of the tungsten grains is 3-8 μm.

3. The copper-tungsten contact material as described in claim 1, characterized in that, The density of the copper-tungsten contact material is ≥99.2%.

4. The copper-tungsten contact material as described in claim 1, characterized in that, The contact material has an electrical conductivity ≥42%IACS, a bending strength ≥1400MPa, and a hardness ≥250HB.

5. A method for preparing a copper-tungsten contact material, characterized in that, Includes the following steps: Tungsten powder and copper powder with a Fisher particle size of 2-5 μm are mixed with multi-component composite additives by high-energy ball milling in a certain proportion to obtain a mixed powder; wherein, according to the mass percentage of the mixed powder, tungsten powder accounts for 75-85%, multi-component composite additives account for 0.3-0.8%, and the balance is copper powder. The mixed powder is cold-pressed to obtain a skeleton compact; The skeleton compact is pre-sintered at high temperature in a hydrogen atmosphere to obtain a sintered skeleton. Oxygen-free copper is placed above the sintered skeleton, heated and pressurized infiltrated in a vacuum furnace, and cooled to obtain the copper-tungsten contact material as described in any one of claims 1-4.

6. The method for preparing the copper-tungsten contact material as described in claim 5, characterized in that, The ball-to-material ratio of the high-energy ball mill is 5:1-8:1, the milling time is 10-20 hours, and the rotation speed is 200-300 rpm.

7. The method for preparing the copper-tungsten contact material as described in claim 5, characterized in that, The high-temperature pre-sintering temperature is 1300-1500℃, the heating rate is 5-10℃ / min, and the holding time is 3-5h.

8. The method for preparing the copper-tungsten contact material as described in claim 5, characterized in that, The pressure infiltration temperature is 1400-1550℃, and the vacuum degree is ≤5×10⁻⁶. - Apply pressure of 5-10 MPa and maintain the temperature for 2-4 hours.

9. A contact, comprising a contact body and a conductive rod, characterized in that, The contact body is made of the copper-tungsten contact material as described in any one of claims 1-4.

10. A contact as described in claim 9, characterized in that, The conductive rod is made of copper-chromium-zirconium alloy.

11. A contact as described in claim 9, characterized in that, The surface of the conductive rod to be welded has a thickness Ra ≤ 1.6 μm.

12. A contact as described in claim 10, characterized in that, The copper-chromium-zirconium alloy comprises, by weight percentage: 0.5-1.2% chromium, 0.08-0.3% zirconium, and the balance being copper.

13. A method for preparing a contact as described in any one of claims 9-12, characterized in that, The method includes the following steps: The contact body and the conductive rod are vacuum diffusion welded together to form an integral contact. The integral contact is subjected to solution aging treatment.

14. The preparation method according to claim 13, characterized in that, The vacuum diffusion welding temperature is 950-1050℃, the pressure is 10-25MPa, and the holding time is 1-3h.

15. The preparation method according to claim 13, characterized in that, The solution aging treatment includes: solution treatment at 980-1020℃ for 1-2 hours followed by water quenching, and aging at 470-500℃ for 3-5 hours.